ICDM for Motion of the Object Detection with GCM Alert over Android Phone (International Journal of Engineering and Computer Science, 2014)
This project has an enhanced feature of smart video transfer and capture character. Smart video surveillance systems are able of enhancing situational awareness across multiple scales of space and time. Video surveillance systems are becoming increasingly important for crime investigation and the number of cameras installed in public space is increasing. However, many cameras inaugurated at fixed positions are required to observe a wide and complicated area. In order to efficiently observe such a wide area at lower cost, mobile robots are an acceptable option. According to the result of moving object detection research on video sequences, the motion of the people is tracked using video surveillance. The moving object is described using the Cauchy distribution model. The Cauchy distribution model will contrast the current frame with the previous frame. The threshold value is determined to find the moving image. Using threshold value the discovered pixel is identified. Hence the motion of the object is identified accurately. After motion discovery, it will send GCM alert to the android mobile application